The genus Ellisolandia (Corallinaceae, Corallinales, Rhodophyta) in the Azores (NE Atlantic): character expression and taxonomic evaluation - Couto, Ruben Pacheco; Rosas-Alquicira, Edgar Francisco; Rodrigues, Armindo Santos; Neto, Ana Isabel (Phytotaxa, 2014)
Morphological and anatomical characters used for segregating species within the genus Corallina (Corallinaceae, Rhodophyta) have been compiled and evaluated in 120 specimens collected in the Azores. The morphological, anatomical and statistical evaluation of the thirty four segregating characters for the genus Corallina performed in the present study revealed no species segregation, either showing no differences across the whole lot of specimens or being highly variable within sets of plants. This suggests that all studied material belongs to one species, so far Ellisolandia elongata (formely Corallina elongata), thus reinforcing old proposed synonyms. A morphological and anatomical account is provided for this species, considering the whole set of studied specimens.